Dynamics of the content of markers of bone tissue metabolism in the oral liquid of patients with injury of the jaw and facial area - Pavlov, S. V.; Semenov, D. M.; Павлов, Сергій Васильович; Семенов, Денис Михайлович (Czech Republic: European Scientific Center Biologial Marker, 2020)
The introduction of minimally invasive, specific and informative methods of diagnosis and monitoring the effectiveness of treatment in modern dental practice is an urgent task of medical science. One of such methods is the study of specific molecules in biological fluids, which are markers of various pathological conditions. Specificity and their informativeness are firstly determined by their participation in the pathogenesis of diseases; secondly – by their appearance during the pathobiochemical reactions [1, 2].
Keywords: MMP8; osteocalcin; FGF23; injuries of the maxillofacial area